2020
DOI: 10.3389/fmed.2020.574842
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Score and Bone Quality in Systemic Lupus Erythematosus Patients

Abstract: Background: Systemic lupus erythematosus (SLE) patients run a higher risk of having low bone mass due to multifactorial events that include physical inactivity, persistent inflammation, low vitamin D levels, and glucocorticoid treatment. This study aimed at obtaining a comparison between bone involvement in SLE patients and healthy matched subjects (HS). Methods: A total of 40 SLE females (average age 54.1 ± 16.3 years) and 40 age-gender matched HS (average age 54.2 ± 15.9 years) were enrolled after having obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Moreover, a high prevalence of morphometric vertebral fractures has been observed in SLE patients, despite the fact that 1/3 of them had normal bone density, in line with the hypothesized multi-factorial etiology of fractures in SLE (14,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Indeed, long-term use of corticosteroids may induce OP in SLE patients by influencing bone turnover (increasing bone resorption and decreasing bone formation), preventing the formation of collagen and osteocalcin, as well as reducing the bone matrix mineralization (14,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Moreover, numerous cytokines are involved in OP pathogenesis, due to their influence on osteoblast and osteoclast function, i.e., IL-33 (35,(37)(38)(39).…”
Section: Tbs and Systemic Lupus Erythematosusmentioning
confidence: 62%
See 4 more Smart Citations
“…Moreover, a high prevalence of morphometric vertebral fractures has been observed in SLE patients, despite the fact that 1/3 of them had normal bone density, in line with the hypothesized multi-factorial etiology of fractures in SLE (14,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Indeed, long-term use of corticosteroids may induce OP in SLE patients by influencing bone turnover (increasing bone resorption and decreasing bone formation), preventing the formation of collagen and osteocalcin, as well as reducing the bone matrix mineralization (14,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Moreover, numerous cytokines are involved in OP pathogenesis, due to their influence on osteoblast and osteoclast function, i.e., IL-33 (35,(37)(38)(39).…”
Section: Tbs and Systemic Lupus Erythematosusmentioning
confidence: 62%
“…Lai et al and Ruaro et al emphasized the important role TBS plays as an innovative and safe diagnostic tool for the quantification of bone quality in chronic and systemic inflammatory rheumatic diseases, such as those observed in SLE. In fact, both studies confirmed that SLE patients have a higher risk of bone loss (osteopenia and OP) and fractures than do HS (34,40).…”
Section: Tbs and Systemic Lupus Erythematosusmentioning
confidence: 68%
See 3 more Smart Citations